Bilaminar technique in the treatment of gingival recession: Case study (Revista Nacional de Odontología, 2018)
Introduction: Gingival recessions cause aesthetic problems and appear due to the displacement of the gingival margin towards the apical wall of the amelocementary limit. They expose the root surfaces, and therefore increase the possibility of root caries, dentinal hyperesthesia and cervical abrasions. They are multifactorial, Miller classified them according to their extension in order to determine the degree of root coverage that could be expected after performing surgical treatment. Purpose: To describe a case of Miller class ii gingival recession located in tooth 44. In this patient, a subepithelial connective tissue graft, covered with a coronally positioned flap was carried out. Materials and method: A female patient with medical history who attended the periodontics service concerned about the “changing position of a tooth’s gum”. She was diagnosed with Miller class ii gingival recession located in tooth 44. Bilaminar technique of subepithelial connective tissue graft, combined with coronally positioned flap of partial thickness was performed. Results: After seven days the patient evolved and the suture was removed from the donor area where sheshowed a good healing process. The patient was therefore told to come again the following week to remove surgical cement and suture from the grafted area; discrete signs of inflammation and complete radicular coverage of 44 were observed. The subsequent appointments after a month, three and six months showed gingival tissue with no inflammation; the gingival recession of tooth 44 was completely covered, there was gain of inserted gum and color harmony between the grafted and adjacent areas. Conclusions: The applied technique proved to have favorable results regarding root coverage, increase in theamount of keratinized gum and appropriate aesthetic appearance
Keywords: gingival recession; subepithelial connective tissue graft; bilaminar technique